The Effect of Productive Zakat Programs on the Wellbeing of Mustahik, with Business income as a Mediating Variable - Anantha, Izdihar Al Mas (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2026)
This study aims to analyze the effect of productive zakat programs on the welfare of mustahik (recipients) with business income as a mediating variable at LAZNAS Nurul Hayat. The background of this study is based on differences in empirical findings related to the effectiveness of productive zakat in improving the welfare of mustahik in a sustainable manner. This study uses a quantitative approach with a survey method, where primary data is collected through questionnaires and analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method. The results show that business capital assistance and entrepreneurial characteristics have a positive and significant effect on the welfare of mustahik and business income. However, business income does not have a significant effect on the welfare of mustahik, so it does not mediate the relationship between independent variables and the welfare of mustahik. These findings indicate that the welfare of mustahik is not only determined by an increase in income, but also by the effectiveness of capital and the characteristics of individual zakat recipients. This study provides practical implications for zakat institutions in designing more targeted and sustainable productive zakat programs.